Pemasyarakatan Narapidana: Melihat Kembali Ke Pemikiran DR. Sahardjo - Petrus Irwan Panjaitan (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
Treating prisoners well and properly in a humane manner is one measure of whether a country is civilized or not, especially if the country is a country based on law like Indonesia. Indonesia as a country of law certainly no longer emphasizes the implementation of punishment as it once did during the colonial era, where Sahardjo said very seriously as in his speech